A research study : on effectiveness in terms of processing in the preparation of XML file using : ekadaster method in certified plan [Building] [PA[B] approval application / Mohd Saflan Zainol Abidin - Zainol Abidin, Mohd Saflan (2018)
The Department of Survey and Mapping Malaysia (DSMM) has issued a new directive to all Licensed Land Surveyors (LLS) throughout Malaysia except in Sabah and Sarawak states that the preparation of strata plan proposals and certified plan of building must be carried out under the eKadaster environment. At the same time, abolished the conventional method from 1st June of 2015, which has been adopted so far to issue strata titles. Although it has been three years passed, there are still many who complain because there are some problems in the generation of the required Extensible Markup Language (XML) files to be submitted with other soft copy files. Hence, a study was conducted to analyze the effectiveness of the processing of this XML file for strata title survey work. The research that outlines four objectives namely, to identify the procedure in generating the XML file; to investigate the problems encountered during the certified plan of building (PA(B)) approval process using the eKadaster method; to compare the differences between new and old manual submission procedure for strata titles application; to evaluate the effectiveness of eKadaster method by using questionnaire of Technology Acceptance Models (TAM). After studying the procedures for generating XML files, conducting interview sessions, and also obtaining feedback from LLS on questionnaires using TAM, all these data were collected, processed and analyzed, then produce findings and results proving that through this eKadaster environment, the preparation of XML files in the PA(B) approval application, is positively effective in terms of the processing. The findings from this study can also be a preliminary assessment to be used as a measure for future improvements for certain parties.